1,2,3 Pancake Enterprise / Nurul Ain Sutiman... [et al.] - Sutiman, Nurul Ain; Merdeka, Ahmad Nijam; Arapa, Atinah (2013)
There are many types of business in the industry. Business are differentiated in term of what they can do, responsibilities, and also taxes. Because of that, in order to open up a new business, we need to look at many aspects to choose the best business structure that suits you. Thus, we have choose a type of business so called partnership organization business. Partnership is unincorporated businesses. The General Manager, Marketing Manager, Operation Manager and financial Manager are the shareholders who run this type of business. They are the main role that plays in this type of business. Partnership distributes all profits and losses to their shareholders without regard for any profits retained by the business for cash flow purpose. Because of that, we are intended to open up a business by establishing a 1,2,3 Pancake Enterprise which sells variety types of pancakes. Our company establishment will be located at lndah Permai. This location is very strategic due to its location that near to housing, universities, and it is the central location for people to buy their daily products. High population is also one of the factors.